2017
DOI: 10.18632/oncotarget.22885
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative metabolomics for investigating the value of polyamines in the early diagnosis and therapy of colorectal cancer

Abstract: As an important biomarker for cancer, polyamine levels in body fluid could be employed for monitoring the colorectal cancer (CRC), however the role of polyamines in the development and therapeutics phases of CRC remains uncertain. In this paper, the relationship between polyamines and CRC development and therapeutics had been investigated by the study of changes in plasma polyamine levels during the precancerous, developmental and treatment phases of CRC. After inducing CRC in Wistar rats by intraperitoneal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Moreover, metabolic profiling of AD brains revealed that there was significant decline in PA concentrations, revealing another aspect of PAs [ 149 , 150 ]. Studies have shown that age-related region-specific decline of PAs in the cerebral cortex is increased by trauma, this directly suggests that PA system dysregulation may contribute to age-related impairments [ 122 , 150 , 151 , 152 , 153 , 154 ]. Moreover, in the serum of AD patients, it was seen that acetylated spermine, a derivative of spermidine, was downregulated [ 155 , 156 , 157 ].…”
Section: Glial-oriented Potential Therapeutic Targets Of Interestmentioning
confidence: 99%
“…Moreover, metabolic profiling of AD brains revealed that there was significant decline in PA concentrations, revealing another aspect of PAs [ 149 , 150 ]. Studies have shown that age-related region-specific decline of PAs in the cerebral cortex is increased by trauma, this directly suggests that PA system dysregulation may contribute to age-related impairments [ 122 , 150 , 151 , 152 , 153 , 154 ]. Moreover, in the serum of AD patients, it was seen that acetylated spermine, a derivative of spermidine, was downregulated [ 155 , 156 , 157 ].…”
Section: Glial-oriented Potential Therapeutic Targets Of Interestmentioning
confidence: 99%
“…In fact, polyamine levels in the urine and serum of CRC patients are higher than those of healthy individuals, suggesting its possible application as a biomarker for early diagnosis. [ 65,66 ] Similarly, spermidine and spermine levels in the colonic mucosa of CRC individuals are threefold higher compared to normal colonic mucosa. [ 67–69 ] Bacteroides spp., Fusobacterium spp., and Escherichia coli are the main bacteria responsible for arginine metabolization to polyamines.…”
Section: Types Of Microbial‐derived Molecules Sources and Bioactivimentioning
confidence: 99%
“…The two-drug treatment alone or co-therapy reversed the levels of 1,3-diaminopropane, cadaverine, and N-acetylputrescine. The team also used this metabolomics method to evaluate the efficacy of Aidi injections on CRC [91]. It was found that Aidi injection treatment could reverse polyamine metabolism, especially agmatine and putrescine, revealing that plasma polyamine could be a biomarker for both early diagnosis and medical treatment of CRC.…”
Section: Other Related Metabolismsmentioning
confidence: 99%